STUDY OF TRANSMISSION LINES EFFECT ON THE SYSTEM OPERATIONON OF CONTINUOUS AUTOMATIC CAB SIGNALLING - Hololobova, O. O.; Havryliuk, V. I.; Kovryhin, M. O.; Buriak, S. Yu. (Science and Transport Progress, 2014)
Purpose. To conduct an effect research of the electromagnetic field of high-voltage transmission lines (HVTL) (750 kV, 50 Hz) on the track circuits and continuous automatic cab signalling (CACS) with a signal current of 50 Hz in the areas of convergence and intersection with the transmission lines and to propose possible methods to improve noise immunity of CACS. Methodology. The measurements were performed both by means of car-laboratory and directly on rail lines. During the study the electric field strength in the range of industrial frequency directly under the transmission lines and at the distance from it to the railway lines was measured, as well as the time dependence of CACS codes with signal current frequency of 50 Hz directly under the transmission lines and at a distance from it in the absence of the train and its passing. Findings. The root causes analysis of CACS faults and failures was carried out. The effect of the electromagnetic field of highvoltage transmission lines (750 kV, 50 Hz) on the track circuit and CACS with signal current of 50 Hz in the areas of convergence and intersection with the transmission line was investigated. Possible methods to improve noise immunity of CACS were considered. Originality. The effect research of transmission lines (750 kV) on the operation of the automatic cab signalling on spans Prishib-Burchatsk and Privolnoye-Yelizarovo, Pridneprovsk railway in places of oblique railroads crossing and transmission lines (750 kV, 50 Hz) was conducted. Electric field strength in the range of industrial frequency directly under the transmission lines and at a distance from it to the railway line, as well as the time dependences of ALSN codes with signal current frequency of 50 Hz directly under the transmission lines and at a distance from it in the absence of the train and as its passing were measured. It was found that CACS codes in track circuits under transmission lines are strongly distorted, as strength measurements of electric field are shown, it can be explained by the electromagnetic field effect of transmission lines on track circuits. Practical value. Possible methods of CACS safety enhancement by improving the reliability of signaling from a track on the locomotive were considered.